Regional Variation of Chronic Kidney Disease in Germany: Results From Two Population-Based Surveys - Nicole Aumann; Sebastian E. Baumeister; Rainer Rettig; Wolfgang Lieb; André Werner; Angela Döring; Annette Peters; Wolfgang Koenig; Anke Hannemann; Henri Wallaschofski; Matthias Nauck; Sylvia Stracke; et al. (Karger Publishers, 2015)
Background/Aims: Due to the increasing prevalence of risk factors for chronic kidney disease (CKD), kidney dysfunction becomes a major public health problem. We investigated the CKD prevalence and determined to what extent the variation of risk factors explains the different CKD prevalence in Germany. Methods: We analyzed data from 6,054 participants, aged 31 to 82 years, from the Study of Health in Pomerania (SHIP-1) in Northeast Germany and the Cooperative Health Research in the Region of Augsburg (KORA F4) Study in Southern Germany. Regional differences in selected percentiles corresponding to the cutpoints for estimated glomerular filtration rate (eGFR, 2) and albumin-to-creatinine ratio (ACR, ≥30 mg/g) were tested using quantile regression models that adjusted for CKD risk factors. Results: The prevalence of decreased eGFRcreatinine-cystatinC (5.9 vs. 3.1 %, p creatinine-cystatinC and high ACR. Conclusions: The CKD prevalence is higher in Northeast than in Southern Germany. Differences in the prevalence of risk factors partly explain the higher disease burden of CKD in Northeast than in Southern Germany.